Explaining Middle Eastern and North African (MENA) Military Responses during the 2011 - 2012 Arab Uprisings. Issue 4 (2nd October 2019) - Hazen, Timothy A.
ABSTRACT: This article examines 20 civil-military variables across 21 Middle Eastern and North African (MENA) countries to better understand military responses during the "Arab uprisings." This project argues that MENA militaries experienced disloyalty or fracturing during the uprisings due to a combination of institutional and societal factors. First, a country's military had to possess certain institutional variables prior to the outbreak of the unrest that laid the foundation for military insubordination, and second, the country's protest movements needed to possess certain societal characteristics during the unrest that increased the opportunity for generals and soldiers to defect from the ruling regime.